TEX10 Promotes the Tumorigenesis and Radiotherapy Resistance of Urinary Bladder Carcinoma by Stabilizing XRCC6 - Sheng Luo; Wenjin Wang; Jingfang Feng; Rui Li (Journal of Immunology Research)
Urinary bladder carcinoma refers to the commonest carcinoma with weak prognostic result for the patient as impacted by the limited treatment possibilities and challenging diagnosing process. Nevertheless, the molecular underpinning of bladder carcinoma malignant progression is still not clear. As a novel core part of pluripotency circuitry, testicular expression 10 (TEX10) plays an actively noticeable effect on reprogramming, early embryo development, and embryonic stem cell self-renewal. Nevertheless, TEX10 expressions and functions within bladder carcinoma are still not known. The present work is aimed at revealing TEX10 expression and biological function within urinary bladder carcinoma and elucidating the potential mechanisms. Results showed that TEX10 is abundant in urinary bladder carcinoma, and its protein level was related to poor disease-free survival in a positive manner. Reduced TEX10 level inhibited urinary bladder carcinoma cell proliferating process and metastasis in vitro and xenograft tumorigenicity in vivo. Notably, TEX10 might regulate carcinoma cell proliferating process and metastasis via XRCC6, thereby controlling the signaling of Wnt/β-catenin and DNA repair channel. Moreover, TEX10 gene knockout reduced the radiotherapy resistance of urinary bladder carcinoma. In brief, this work revealed that TEX10 could exert a significant carcinogenic effect on urinary bladder carcinoma tumorigenesis and radiotherapy resistance through the activation of XRCC6-related channels. Accordingly, targeting TEX10 is likely to offer a novel and feasible therapeutically related strategy for inhibiting urinary bladder carcinoma tumorigenicity.